Real-time monitoring system for blood pressure monitoring based on internet of things - Ngurah Desnanjaya, I Gusti Made; Aditya Nugraha, I Made (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Blood pressure is an important cardiovascular health indicator, with normal values set by the WHO at 140 mmHg for systole and 90 mmHg for diastole. Excess of these values indicates hypertension, which increases the risk of serious medical complications. This research developed an internet of things (IoT)-based blood pressure monitoring device, which facilitates digital blood pressure measurement and data transmission to widely accessible applications and websites. The device uses an MPX5050GP pressure sensor, Arduino Nano, and NodeMCU ESP32, as well as other components programmed using the Arduino IDE. Test results obtained from 10 subjects, the device showed an average difference in systole of 7.9 mmHg and diastole of 5.4 mmHg. This complies with recognized accuracy standards of a maximum error of 10 mmHg and indicates that the device operates effectively with the designed concept.